“Elaboracion de un alimento fomulado a base de extracto de malta para alimentacion de niños en edada Pre.Escolar - Delgado Mesia, José Enrique (1997)
The present work is of the formulation and evaluation mathematical of seven (07) mixtures alternative containing proportions variables of extract of malta in powder (E), pollen (P), egg whole of hen (H). cocoa powder (C), skim milk powder (L), brown sugar (A), lecithin (LS) granulated soy and soy protein isolated from dust (PS), expressed in dry base. Were selected three mixtures by the criterion of best value nutritional destined to the feeding of children of age Pre school. The appropriate parameters for the flow of processing, characterization, and control during storage of the product was: formulation, heavy, mixed, load of trays, drying air temperature of 100 ° C for 45 minutes, cooling, grinding, packaging and stored. The content of proteins mixtures (finished product), fluctuate from 19.25 to 20.53% in dry basis, being the limiting amino acid, lysine and protein score average of 88.2%; 30 g of the product is...